Sex differences in biochemical contents of telfaira occidentalis hook F. (2006)
In order to evolve ways of early sex identification in Telfairia, the biochemical contents of leaf, vine and root of male and female plants were determined in three genotypes. Female plants had significantly higher concentrations of protein and fat while the male plant was higher in fibre, as hand all the anti-nutrients. The concentration of trypsin inhibitor was most influential in distinguishing between the sexes especially for root and vines while the fibre content was most important for the leaf. Leaf fibre content is therefore recommended for sex identification since it can be easily determined at any stage of plant development without destroying the whole plant.